A Note on the Górnicki-Proinov Type Contraction - Erdal Karapınar; Manuel De La Sen; Andreea Fulga (Journal of Function Spaces)
In this paper, we propose a notion of the Górnicki-Proinov type contraction. Then, we prove the uniqueness and existence of the fixed point for such mappings in the framework of the complete metric spaces. Some illustrative examples are also expressed to strengthen the observed results.